Quantum systems in chemistry and physics - Wilson, S. (Stephen), 1950- (Advances in quantum chemistry, 1999)
The description of quantum systems is fundamental to an understanding of many problems in chemistry and physics. This volume records a representative slection of the papers delivered at the second European Workshop on Quantum Systems in Chemistry and Physics which was held at Jesus College, Oxford, April 6-9, 1997. The purpose of this international Workshop was to bring together chemists and physicists with a common interest--the quantum mechanical many-body problem--and to encourage collaboration and exchange of ideas on the fundamentals by promoting innovative theory and conceptual development rather than improvements in computatorial techniques and routine applications. Key Features * Covers the following topics: * Density matrices and density functional theory * Electron correlation * Relativistic effects * Valence theory * Nuclear motion * Response theory * Condensed matter * Chemical reactions.